KEMAMPUAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 20 PEKANBARU - Santi Asti Reni; Abdul Razak; Charlina Charlina (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study examines the ability to write explanatory text of students of class VIII SMP Negeri 20 Pekanbaru. The purpose of this study is to describe how high the ability to write text explanation of students of class VIII SMP Negeri 20 and describe the differences in the ability to write explanatory text between groups or between classes. The number of population in this study is 140 while the number of samples in this study that is 104. Research results when tested using t test is the ability to write explanatory text equal to the value of comparison. The comparative score applied in this study was 68. Students' writing ability was the same as comparative score, which means that the ability to write explanatory text of grade VIII students was low. In other words the hypothesis is accepted. Then tested using one way anova. The result is that there is no difference in the ability of writing explanatory text of class VIII students between classes. Based on the results of research authors to note that the ability to write students are low because students do not understand the procedure of paragraph breaking is good and right. Writer presume students often make misleading clarification does not support the main sentence. In addition, in terms of spelling and the use of punctuation needs to be re-evaluationKey Word : ability, writing, text explanation, student